Prph2 disease mutations lead to structural and functional defects in the RPE. Issue 5 (28th March 2022) - Tebbe, Lars; Sakthivel, Haarthi; Makia, Mustafa S.; Kakakhel, Mashal; Conley, Shannon M.; Al‐Ubaidi, Muayyad R.; Naash, Muna I.
Abstract: Prph2 is a photoreceptor‐specific tetraspanin with an essential role in the structure and function of photoreceptor outer segments. PRPH2 mutations cause a multitude of retinal diseases characterized by the degeneration of photoreceptors as well as defects in neighboring tissues such as the RPE. While extensive research has analyzed photoreceptors, less attention has been paid to these secondary defects. Here, we use different Prph2 disease models to evaluate the damage of the RPE arising from photoreceptor defects. In Prph2 disease models, the RPE exhibits structural abnormalities and cell loss. Furthermore, RPE functional defects are observed, including impaired clearance of phagocytosed outer segment material and increased microglia activation. The severity of RPE damage is different between models, suggesting that the different abnormal outer segment structures caused by Prph2 disease mutations lead to varying degrees of RPE stress and thus influence the clinical phenotype observed in patients.